Challenges to stimulate creativity in teaching innovation - Pinto, Miriam de Magdala; Fonseca, Letícia Pedruzzi; Silveira, Priscila Ricardo dos Santos da (Farol, 2024)
Innovation, nowadays, is essential to overcome the challenges that humanity faces in social, environmental and economic terms. To innovate, it is essential to be creative. Creativity can be taught and, in this article, we investigate the methodological proposal and the performance of the Innovation and Entrepreneurship Project Workshops - OPInE in stimulating the creativity of young people when creating innovative projects for their territories or municipalities. The research methodology was based on an online survey of six trainers who participated in the design and implementation of the OPInE training. The survey focused on aspects related to stimulating or blocking creativity. The creativity released was assessed by the trainers' perception of the originality of the projects. The main conclusion is that in the process of teaching innovation, the great challenge is to release the creativity of the learners.
Keywords: active methodologies; innovation projects; stimulation of creativity